The inflammatory milieu within the pancreatic cancer microenvironment correlates with clinicopathologic parameters, chemoresistance and survival. Issue 1 (December 2015) - Delitto, Daniel; Black, Brian; Sorenson, Heather; Knowlton, Andrea; Thomas, Ryan; Sarosi, George; Moldawer, Lyle; Behrns, Kevin; Liu, Chen; George, Thomas; Trevino, Jose; Wallet, Shannon; et al.
Abstract Background The tumor microenvironment impacts pancreatic cancer (PC) development, progression and metastasis. How intratumoral inflammatory mediators modulate this biology remains poorly understood. We hypothesized that the inflammatory milieu within the PC microenvironment would correlate with clinicopathologic findings and survival. Methods Pancreatic specimens from normal pancreas (n  = 6), chronic pancreatitis (n  = 9) and pancreatic adenocarcinoma (n  = 36) were homogenized immediately upon resection. Homogenates were subjected to multiplex analysis of 41 inflammatory mediators. Results Twenty-three mediators were significantly elevated in adenocarcinoma specimens compared to nonmalignant controls. Increased intratumoral IL-8 concentrations associated with larger tumors (P  = .045) and poor differentiation (P  = .038); the administration of neoadjuvant chemotherapy associated with reduced IL-8 concentrations (P  = .003). Neoadjuvant therapy was also associated with elevated concentrations of Flt-3 L (P  = .005). Elevated levels of pro-inflammatory cytokines IL-1β (P  = .017) and TNFα (P  = .033) were associated with a poor histopathologic response to neoadjuvant therapy. Elevated concentrations of G-CSF (P  = .016) and PDGF-AA (P  = .012) correlated with reduced overall survival. Conversely, elevated concentrations of FGF-2 (P  = .038), TNFα (P  = .031) and MIP-1α (P  = .036) were associated with prolonged survival. Conclusion The pancreatic cancer microenvironment harbors a unique inflammatory milieu with potential diagnostic and prognostic value.